Type I and III Interferon Productions Are Impaired in X-Linked Agammaglobulinemia Patients Toward Poliovirus but Not Influenza Virus - Luk, Anderson Dik Wai; Ni, Ke; Wu, Yuet; Lam, Kwok-Tai; Chan, Koon-Wing; Lee, Pamela P.; Tu, Wenwei; Mao, Huawei; Lau, Yu Lung (Frontiers in Immunology, 2018)
Background X-linked agammaglobulinemia (XLA) is a primary immunodeficiency caused by Bruton’s tyrosine kinase (BTK) mutation. Patients are susceptible to severe enterovirus infections. The underlying mechanism remains unknown. BTK is involved in toll-like receptors (TLRs) pathway, which initiates antiviral responses including interferon (IFN) productions. Objective To demonstrate type I and III IFN productions in dendritic cells of XLA patients is decreased in response to oral poliovirus vaccine (OPV) but not H1N1 virus. Methods Monocyte-derived dendritic cells (DCs) were derived from 9 XLA patients aged 22-32 years old and 23 buffy coats from Hong Kong Red Cross blood donors. LFM-A13 was used to inhibit BTK. OPV Sabin type 1 and H1N1 influenza virus were used to stimulate DCs with RPMI as mock stimulation. The antiviral cytokine productions and phenotypic maturation of DCs were determined 24 hours post-stimulation. OPV RNA was determined at 0, 6, 12 and 24 hours post-stimulation. Results Upon OPV stimulation, IFN-α2, IFN-β and IFN-λ1 productions in DCs from XLA patients and BTK-inhibited DCs of healthy controls were significantly lower than that from healthy controls. Whereas upon H1N1 stimulation, the IFN-α2, IFN-β and IFN-λ1 productions were similar in DCs from XLA patients, BTK-inhibited DCs of healthy controls and healthy controls. The mean fluorescent intensities (MFI) of CD83, CD86 and MHC-II in DCs from XLA patients in response to OPV was similar to that in response to mock stimulation, while the MFI of CD83, CD86 and MHC-II were significantly higher in response to H1N1 stimulation than that in response to mock stimulation. Whereas, the MFI of CD83, CD86 and MHC-II in DCs of healthy controls were significantly higher in response to both OPV and H1N1 stimulation compared to that in response to mock stimulation. Conclusion Production of type I and III IFN in response to OPV was deficient in DCs from XLA patients but was normal in response to H1N1 due to deficient BTK function. Moreover, phenotypic maturation of DCs from XLA patients was impaired in response to OPV but not to H1N1. These selective impairments may account for the unique susceptibility of XLA patients towards severe enterovirus infections.